2015
DOI: 10.1002/ceat.201400792
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Two High‐Shear Impellers in an Unbaffled Stirred Tank

Abstract: High-shear impellers (HSIs) are mixers used in industrial stirred tanks to incorporate powders into liquids and break down particle agglomerates. A detailed numerical study of two commercial ring-style HSIs of laboratory scale was carried out and their performance was compared with the Rushton turbine (RT). It was found that power and pumping numbers or their ratio cannot be simply connected for properly selecting an impeller in applications where highly localized viscous dissipation is desirable. The ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
3
19
0
2
Order By: Relevance
“…In a later work, Ramírez‐Muñoz et al performed experiments to investigate the influence of the viscous dissipation on the amount of fines generated from mineral powders. In agreement with Ramírez‐Gómez et al , they found that, based on the effects on the breakage of particle agglomerates, the volume swept by the blades is the region of maximum effective viscous dissipation.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…In a later work, Ramírez‐Muñoz et al performed experiments to investigate the influence of the viscous dissipation on the amount of fines generated from mineral powders. In agreement with Ramírez‐Gómez et al , they found that, based on the effects on the breakage of particle agglomerates, the volume swept by the blades is the region of maximum effective viscous dissipation.…”
Section: Introductionsupporting
confidence: 85%
“…The study was carried out in the transitional flow regime (20 ≤ Re ≤ 133). In previous works , , it has been reported that in this flow regime the laminar model practically delivers the same predictions as a transitional flow model, but with a lower computational cost. Therefore, in this study only the laminar model was used in all simulations.…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations